Rheumatoid Arthritis, Depression, and the Role of Celecoxib - Nadeen Al-Baz (14152428) (2022)
Rheumatoid arthritis (RA) is a chronic autoimmune disease, causing joint destruction and associated physical, mental, and financial distress. Depression is not uncommonly found in patients with RA as both disorders share sociodemographic, functional, and biologic factors. There is growing evidence on the role of anti-inflammatory agents in managing depression, particularly celecoxib, which has been shown to significantly alleviate depressive symptoms as an augmenting agent. Compared with traditional nonsteroidal anti-inflammatory drugs (tNSAIDs), however, celecoxib offers modest improvement in clinical symptoms, with uncertain results for pain management, physical function, and adverse effects in patients with RA. Further research is needed to assess the effectiveness of celecoxib in the management of RA, particularly in patients suffering from comorbid depression. Other Information Published in: SN Comprehensive Clinical Medicine License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s42399-020-00468-w